Public–private partnerships as catalysts for green infrastructure: a three-pronged analysis of economic, environmental, and institutional factors - Owojori, Oluwatobi Mary; Erasmus, Lourens Jacobus (Frontiers in Sustainable Cities, 2025)
As cities contend with the escalating challenges of climate change, rapid urbanization, and resource depletion, the need for sustainable infrastructure solutions has never been more urgent. Cities account for 75% of global CO2 emissions, yet efforts to implement green solutions remain fragmented. Green public–private partnerships (PPPs) offer a sustainable solution, but the mechanisms for effectively leveraging these collaborations remain underexplored. Despite growing interest in PPPs, a critical knowledge gap persists: how is PPP leveraged in tackling crucial urban challenges for advancing green infrastructure? This study critically examines how PPPs drive progress in six key sectors: renewable energy, sustainable urban mobility, water management, waste management, green building and urban greening. Through qualitative case studies, the study analyses flagship projects from cities in both developed and developing countries. The study presents that green PPPs will thrive when backed by strong institutional frameworks, long-term financial commitments, and adaptive collaborative environments. The key to sustainable urban futures lies not just in government action but in strategic PPPs. This study makes a call to rethink urban partnerships—aligning private sector innovation with public mandates. It offers actionable insights for policymakers, urban planners, and investors, demonstrating that green PPPs are catalysts for urban sustainability and if scaled effectively, they could redefine the trajectory of sustainable development.